EFEKTIVITAS PENURUNAN KADAR DODESIL BENZEN SULFONAT (DBS) DARI LIMBAH DETERJEN YANG DIOLAH DENGAN LUMPUR AKTIF - Ni G. A. M. Dwi Adhi Suastuti (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2010)
This research aims to find out the decrease effectivity of dodecil benzene suphonate (DBS) concentrationfrom detergent waste treated using activated sludge. This research was carried out in two steps : the first step wasseeding process or preparation of the activated sludge. This was carried out on plastic container of 2 L. About 3 gsediment taken from Tukad Mati, 1 g NPK were mixed in a plastic container. The volume was made 1 L by addingaquadest, the mixture was aerated for 1 week. The second step was treatment of detergent waste which was carriedout using 2 plastic container of 5 L each. About 2 L detergent waste and 1 L activated sludge solution were mixed inthe plastic container. Mean while, 3 L detergent waste as a control were palced in the other plastic container. Bothcontainer were aerated for observation for decrease DBS concentration was carried out during 0, 3, 5, 7, 10 and 15days. DBS concentration was analyzed using Methylen blue method.The research result indicated that generally, there were decrease of BDS concentration both in control andtreated samples. The lowest DBS concentration was observed on day 15 both on control and treated samples withvalue, of 46.726 and 0.381 mg/L respectively. The decrease effectivity were 8.18% for control and 99,25% fortreated samples. From this research, it can be seen that treatment of waste using activated sludge was effective todecrease DBS concentration in detergent containing waste.